ASSESSMENT OF MULTI-CULTIVARS OF CARAWAY USING TERNARY PLOT UNDER ARID ZONE CIRCUMSTANCES - Cheyed, S.H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
The certain crop cultivars could be adapted that characterized their performance via given trait over given environments. Thus this adaptation could be investigate by many methods. Therefore, ternary plot method advocated to assess the adaptation of ten caraway cultivars using seed yield (Mg ha-1) over two environments viz. Fallujah and Ramadi for two successive seasons (2011/2012 and 2012/2013). This method was fortified with AMMI Biplot technique. PAST software was adopted to construct triangle graph. Cropstat7.2 software was also applied to extract cultivars own biplots. Results from ternary plot showed that G7 was the both most adaptable cultivars over most circumstances, G3 irresponded because it located on point of cross of triangle diameters. G4 was semi adaptable. While, G3 was the average genotype due to be laid on cross point of triangle. Thus, it could be concluded that ternary plot and AMMI biplot were effectively explained the stable and adaptable genotypes of caraway multienvironment trial and supplemented each other. Therefore, it could be recommended to apply suitable biplot as AMMI technique supplemented with simple statistics parameters as quantiles fortified by ternary plot.